Analysis of Temperature Distribution and Mechanical Properties of Friction Stir Welding of Al-Cu Joints Using Hardened H13 Steel Tools - J. Pratap Kumar; Anil Raj; A. R. Venkatraman; Arul Kulandaivel; G. Ashwin Prabhu; S. K. Narendranathan; Nagaraj Ashok (Advances in Materials Science and Engineering)
Friction Stir Welding (FSW) is a superior metal joining technique for joining similar and dissimilar metals. The various materials acceptable for the FSW techniques were magnesium alloys, mild steel, stainless steel, copper alloys, titanium alloys, aluminium alloys, etc. In this method, the frictional heat generated by the tool on metal workpieces was used for joining, and the workpieces were joined below the upper critical temperature. The substantial benefit of this technique is that it is capable of welding unweldable alloys by the conventional fusion welding method. The welding tool was rotated, traversed, and penetrated into the joint between two base plates. A suitable tool design with appropriate process parameters will result in high-quality welding on workpieces. In these experiments, the tools were designed with different pin profiles. The welding tools required for FSW are designed using SOLIDWORKS, and temperature distributions across the weld regions were analyzed using Ansys software. The fixture needed for FSW is fabricated according to machine requirements. The tool material used was hardened H13 steel, and the base plates were aluminium alloy 6101 and copper alloy C11000. The temperature distributions are noted in each trial during FSW of Al-Cu joints along the weld line region. Due to maximum temperature at weld joints, high ultimate tensile strength and impact strength were obtained at 1200 rpm tool rotational speed and 20 mm/min feed rate with the square pin profile of a hardened H13 steel tool. The obtained ultimate tensile stress (UTS) at joints was less than that of the base plates Al and Cu. The microhardness value was higher at the nugget zone than at the base plates, giving high strength at the joint area and unevenly distributed.